2014
DOI: 10.15288/jsad.2014.75.889
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Among Young Adult Children From Alcoholic Families

Abstract: ABSTRACT. Objective: Given the evidence that several cognitive and emotional functions are impaired in adult alcohol-dependent patients and the possibility that some of these defi cits are transmitted to their children, the objective of the present study was to test the hypothesis that the perception of complex mental states would be reduced in young adults from families with a positive family history of alcohol dependence. It was also anticipated that social-perceptual defi cits would confer unique predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Like Lyvers et al, Demers and Koven found that EOT uniquely and negatively predicted variance in both facial emotion recognition (as indexed by RMET) and an index of emotional empathy that was similar to EC. Maurage et al (2011) reported that facial emotion recognition performance on the RMET was impaired in detoxified clients undergoing treatment for alcohol dependence compared to controls, a finding consistent with evidence of theory of mind deficits in alcohol use disorders (Kopera et al, 2014;Onuoha et al, 2016). Given the strong associations of trait alexithymia with alcohol and other substance use disorders (Lyvers, Hinton et al, 2014;Thorberg et al, 2009;Thorberg et al, 2016), deficient facial emotion recognition in an alcohol-dependent sample would seem plausibly attributable to the high levels of alexithymia commonly found in such samples; however, Maurage et al reported that the RMET performance of their alcohol dependent sample was independent of alexithymia and other trait factors.…”
mentioning
confidence: 62%
“…Like Lyvers et al, Demers and Koven found that EOT uniquely and negatively predicted variance in both facial emotion recognition (as indexed by RMET) and an index of emotional empathy that was similar to EC. Maurage et al (2011) reported that facial emotion recognition performance on the RMET was impaired in detoxified clients undergoing treatment for alcohol dependence compared to controls, a finding consistent with evidence of theory of mind deficits in alcohol use disorders (Kopera et al, 2014;Onuoha et al, 2016). Given the strong associations of trait alexithymia with alcohol and other substance use disorders (Lyvers, Hinton et al, 2014;Thorberg et al, 2009;Thorberg et al, 2016), deficient facial emotion recognition in an alcohol-dependent sample would seem plausibly attributable to the high levels of alexithymia commonly found in such samples; however, Maurage et al reported that the RMET performance of their alcohol dependent sample was independent of alexithymia and other trait factors.…”
mentioning
confidence: 62%
“…Indeed, earlier studies have suggested that ToM impairments might be influenced by the duration of alcohol dependence, by the intensity of alcohol consumption, and by current craving for alcohol (Maurage et al., ). In the same vein, while it has been shown that ToM impairments are not present in high‐risk populations (i.e., children of ALC) before the development of alcohol dependence (Kopera et al., ), the causal link between ToM impairments and alcohol dependence should be further investigated, particularly in longitudinal studies. In addition, future research should explore the psychological processes responsible for affective ToM impairments and determine whether this deficit originates at the perceptual (e.g., inaccurate visual analysis of emotional scene), identification (e.g., wrong interpretation of affective cues), or mnesic (e.g., erroneous matching with memorized emotional labels) level, notably in view of the large‐scale metamemory impairments observed in this population, which might influence social interactions (LeBerre et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter one, based on a multilevel assessment of ToM, described a generalized ToM deficit in alcohol dependence, including first‐person (i.e., identifying one's own feelings) and third‐person (i.e., identifying others' feelings) levels, as well as first‐order (i.e., understanding what others feel about an external event) and second‐order (i.e., understanding what others feel about another individual's feelings) perspectives. It is also worth noting that this ToM impairment is not present among non‐alcohol‐dependent young adults with alcohol‐dependent parents, suggesting that these impairments might be the direct consequence of installed alcohol dependence (Kopera et al., ). As a whole, and as further confirmed by a recent meta‐analysis (Onuoha et al., ), alcohol dependence appears to be directly associated with large‐scale impairments in ToM abilities, which might be partly underpinned by cognitive impairments (e.g., autobiographical memory [Nandrino et al., ]).…”
mentioning
confidence: 98%
“…Although this finding suggests that deterioration or poor development of the decision‐making processes can occur before the emergence of AUD, it does not negate the hypothesis that decision making is also negatively affected as a result of chronic heavy drinking. Not all deficits, however, show a relationship with a positive family history of alcohol; for example, ToM impairment was not more prevalent in children of alcohol‐dependent parents (Kopera et al., ). Exploration of links between cognitive performance and alcohol use variables (i.e., length of alcoholism, usual daily alcohol intake, or number of withdrawals; cf., Duka et al., ; Loeber et al., ) could also constitute other ways to investigate this question.…”
Section: Limitations Of Knowledge To Date and Issues To Considermentioning
confidence: 99%